Handbook of enterprise systems architecture in practice - Saha 1970- (Information Science Reference, 2007)
"This book is a valuable addition to the reading list of executives, managers, and staff in business, government, and other sectors who seek to keep their enterprises agile and efficient as they manage change, implement new business processes and supporting technologies, and pursue important strategic goals"--Provided by publisher